Inflammatory bowel disease in young patients: challenges faced by black and minority ethnic communities in the UK. (9th February 2015) - Alexakis, Christopher; Nash, Avril; Lloyd, Michele; Brooks, Fiona; Lindsay, James O.; Poullis, Andrew
Abstract There is strong evidence indicating that inflammatory bowel disease (IBD) is increasing among black and minority ethnic (BME) communities. Despite this rise in prevalence, there is a paucity of research relating to ethnicity and IBD outside the USA. Furthermore, the symptoms of IBD are reported to start during childhood or adolescence in 20–25% of people with the condition. It is therefore important that young people's experiences of diagnosis, treatment and living with IBD are fully understood to ensure effective services and information provision. The study reported on in this paper was commissioned by a UK charity (Crohn's and Colitis UK) with the aim of increasing understanding of the specific issues and service needs of young people with IBD from BME communities. Empirical research entailed in‐depth semi‐structured interviews with 20 young people from BME groups accessed through gastroenterology departments at three collaborating NHS hospitals in England serving ethnically diverse populations. Interviews were carried out from June to December 2010 and sought to capture young people's views with IBD. A thematic analysis of their experiences identified many commonalities with other young people with IBD, such as the problematic route to formal diagnosis and the impact of IBD on education. The young people also experienced tensions between effective self‐management strategies and cultural norms and practices relating to food. Moreover, the ability of parents to provide support was hampered for some young people by the absence of culturally competent services that were responsive to the families' communication needs. The findings highlight the need for more culturally appropriate information concerning IBD, and improved responsiveness to young people with IBD within primary care and the education system, as well as culturally competent messaging relating to the specific nature of the condition among the wider South Asian and black communities.